REGISTRY MANAGEMENT PROGRAM FOR ISCHEMIC HEART DISEASE IN ALTAISKY KRAY - Е. A. Nomokonova; V. A. Elykomov; A. A. Efremushkina; Е. G. Nikulina; К. V. Nedoseko (Российский кардиологический журнал)
Aim. To evaluate  the  results  of the  program  for management of ischemic  heart disease registry in Altaisky kray in 2011-2015 y.Material and methods. The system was developed and implemented in 2011 as a pilot project,  with software named  “Monitoring + [Registry of CIHD]”. The project was planned  as  retro-,  prospective  observational  cohort  study.  The registry was primarily tested on  the  bases of Regional  Clinical Hospital and  Altai Regional Cardiological Dispensary.  From the beginning of 2014, other 28 institutions were involved into  the  registry.  The  work is  being  done  continuously,  with patients admission and investigation if fulfill the registry criteria. For statistics the descriptory methods  were applied.Results  and  discussion. From 2011  to 2015,  the  data  of 12886  patients  was entered to the registry, with the diagnosis  “ischemic heart disease”. Mean age — 65,1±9,9  y.o. Region capital citizens were 35,5% of the registry, and inhabitants of the  Region — 64,5%.  Two thirds were males.  By the  anamnesis data,  there  was significantly more  persons after  myocardial  infarction  — 7094  (p<0,01).  Hightechnology care under “Cardiovascular surgery” unit was provided to 6115 (47,4%) patients.  Medication treatment was done according  to guidelines and standards for ischemic heart  disease patients  management. With the implementation  of registry, availability of cardiovascular care for rural inhabitants improved: three times increased the volumes of outpatient stage high-technology care, and cardiosurgery increased 1,8 times. The decrease of cardiovascular mortality during last 5 years reached 18,6%. Conclusion. A  universal  approach has  been  formulated  for a  unified base  of patients  suffering  from ischemic  heart  disease, that  makes  it to  follow-up the epidemiological situation in districts of Region by disease, to find out the risk factors and correct them. With the Registry of CIHD, it is possible to analyze the performance of cardiological care, to influence on its qualitative and quantitative parameters. The necessity  is shown, for the development  of this monitoring system in all treatmentprevention  institutions of the Region for equality in specialized  care  accessibility, including high-technology care.